Uma gramática visual para o fotojornalismo - Câmara, Mônica (2010)
This work is about the presence of language in the discourse of photographic images, photographs of information, specifically. By supporting the idea that images can speak, narrate facts, provoke our senses. We will analyze some photojournalistic images produced by the author of this research for the Diário Paraibano O Norte (2001 through 2006), showing its semiotic implications through Peirce’s theory of signs (1995); its syntactic-imagery structure, understood and manipulated by the Visual Grammar of Kress and van Leeuwen (1996); possible formalizations on the aesthetic experience which is also covered in this type of text (BARILLI, 1994; SILVA, 2010); as well as showing discursive performances with syntactic and aesthetic effect (KRESS and van LEEUWEN, 1996; BARILLI, 1994; SILVA, 2010).